ANALISIS PENGARUH HARGA PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA BANGKA TRADE CENTER PANGKALPINANG (STUDI KASUS : TOKO PAKAIAN SUGIANTO) - Vania, Della; Panjaitan, Fery; R. Manullang, Rizal (Jurnal Progresif Manajemen Bisnis, 2024)
This thesis was written and prepared by Della Vania with Student Identification Number 230200014 entitled “Analysis of the Effect of Product Price and Service Quality on Consumer Satisfaction at the Bangka Trade Center Pangkalpinang (Case Study : Sugianto Clothing Store). This research was conducted from January to June The aim of this research is to determine the effect of product price and service quality on consumer satisfaction at the Bangka Trade Center Pangkalpinang. This research uses a quantitative descriptive approach method. Data was collected by distributing questionnaires to 80 respondents in this study who were consumers of the Bangka Trade Center Pangkalpinang. The sample was determined using the Purposive Sampling technique. Data analysis used Validity Test, Reliability Test, Classic Assumption Test, Multiple Linear Regression Test, Simultaneous Test (F Test) and Partial Test (t Test) processed with JASP. From the research results obtained from the three independents, namely product price and service quality, both products and service quality have a positive value for consumer satisfaction except price. Based on the partial significance test (t test), product and service quality partially influence customer satisfaction except for price. It can be concluded that service quality variables simultaneously influence customer satisfaction.